2015
DOI: 10.1103/physrevb.92.155133
|View full text |Cite
|
Sign up to set email alerts
|

Long-range order and symmetry breaking in projected entangled-pair state models

Abstract: Projected Entangled Pair States (PEPS) provide a framework for the construction of models where a single tensor gives rise to both Hamiltonian and ground state wavefunction on the same footing. A key problem is to characterize the behavior which emerges in the system in terms of the properties of the tensor, and thus of the Hamiltonian. In this paper, we consider PEPS models with Z2 onsite symmetry and study the occurence of long-range order and spontaneous symmetry breaking. We show how long-range order is co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…20. This was studied previously in finite systems on a cylinder [50]. We observe that, first, there is a unique lowest entanglement eigenvalue (or one unique largest eigenvalue of corresponding transfer matrix), which is clearly identified by our method.…”
Section: Chiral Topological Corner Entanglement Spectrummentioning
confidence: 63%
See 3 more Smart Citations
“…20. This was studied previously in finite systems on a cylinder [50]. We observe that, first, there is a unique lowest entanglement eigenvalue (or one unique largest eigenvalue of corresponding transfer matrix), which is clearly identified by our method.…”
Section: Chiral Topological Corner Entanglement Spectrummentioning
confidence: 63%
“…In Ref. [50] it was shown that there is a second-order quantum phase transition from ordered phase to disorder phase occurring at θ c ≈ 0.349596. To illustrate that our method is not limited by the usage of corner tensors, we include results from the 2d Ising PEPS in the disorder phase with θ = 0.5 in Fig.…”
Section: Chiral Topological Corner Entanglement Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…The framework of MPS and PEPS naturally provides an efficient method to classify topologically ordered phases 17,18 , symmetry protected topological phases [19][20][21] , and the long-range ordered phases with spontaneous symmetry breaking 19,22 . However, it is not straight forward to extend the MPS representation to the one-dimensional parafermion systems.…”
Section: Introductionmentioning
confidence: 99%